BOOK TAX DIFFERENCES AND EARNING QUALITY - Khoridha Rizky Amalia Panda; Nur Diana (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research is to examine empirically the influence ofbook tax differences to earning quality. In this study, Book Tax Differencesdivided to two groups: permanent differences and temporary differences, whilefor earning quality is proxies with Earning Response Coefficient (ERC).Population in this research are manufacturing companies in IndonesianStock Exchange in period of 2014-2016. With purposive sampling method,samples used are 23 manufacturing companies for three years, so the total samplein this research are 69 samples. The data used in this research is secondary datawith engineering documentation. Methods of statistical analysis used multipleregression using the program SPSS for windows.The results show that permanent differences variable and temporarydifferences variable simultaneously had a significant effect on earning quality(ERC). While partially, temporary differences significantly affect the earningquality (ERC) and permanent differences not significantly affect the earningquality (ERC).Keywords : Permanent Differences, Temporary Differences, EarningQuality, Earning Response Coefficient.